The Effect of Administrating “MAPIA” Date Juice (Phoenix dactylifera L.) Mixed with Ambon Bananas (Musa paradisiaca var. Sapientum Linn) on Blood Pressure Reduction in Hypertensive Patients - Ika Satriani; Ni Ketut Sri Sulendri; Joyeti Darni; Suhaema Suhaema (Jurnal Gizi Prima (Prime Nutrition Journal), 2026)
Background: Hypertension is a vascular disorder that impedes the supply of oxygen and nutrients. This condition requires special attention as hypertension is a significant factor in the occurrence of stroke, coronary heart disease, and kidney disease. One way to increase potassium intake is through the consumption of fruits and vegetables. The intervention using food ingredients such as dates and Ambon bananas is expected to enhance patients’ potassium intake, thereby helping to monitor and manage blood pressure. Research Methods: The study employed a quasi-experimental design with a non-equivalent control group. The intervention involved administering Mapia juice to the intervention group for 7 days, whilst a control group was selected based on inclusion criteria using a regional approach. This was done to determine whether there were differences between the intervention and control groups. Research Results: The Mann-Whitney test results revealed significant differences in systolic blood pressure between pre- and post-intervention measurements in the intervention group (10.9 ± 0.36 mmHg) compared to the control group (1.3 ± 1.35 mmHg), with a p-value of 0.000. Similarly, diastolic blood pressure showed significant differences between the intervention group (7.95 ± 2.42 mmHg) and the control group (0.1 ± 0.24 mmHg), with a p-value of 0.000. Conclusion:  The results indicate a significant effect between the intervention and control groups on both systolic and diastolic blood pressure measurements.